Agenda for peace - Boutros-Ghali, Boutros (UN New YorkUS, 1992)
Addresses topics such as preventative diplomacy, peacemaking, and post-conflict peace-building. Looks also at cooperation with regional arrangements and organizations as well as the safety of United Nations personnel.